Enhancing Biology Learning Outcomes through the Implementation of the Predict-Observe-Explain (POE) Instructional Model - Rizki Amalia Nur; Nurhidayah Nurhidayah; Rika Riyanti (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Learning models play an important role in providing opportunities for students to be actively involved in exploring and applying everyday Biology concepts. One of the effective learning models is Predict-Observe-Explain (POE), which focuses on developing students' life skills. This study aims to evaluate the effectiveness of the POE learning model in improving Biology learning outcomes, especially in the context of the excretory system. This research is a pseudo-experimental study that focuses on the variable of students' Biology learning outcomes, applying the POE learning model. This research methodology uses Pretest-Posttest Group Design. The population of this study was all VIII grade students at MTsS Darul Istiqamah Gowa, with two classes consisting of 22 students each. The analysis results showed that the experimental class, which used the POE learning model, had better learning outcomes than the control class. This improvement can be seen in both classes' minimum, maximum, and average values. Based on the results of this analysis, it can be concluded that there is a significant increase in learning outcomes for students who apply the POE learning strategy compared to students who do not.